Integrating ICT to Improve Student Outcomes in Diverse Classrooms - Yuniwati, Ika; Hussain, Sara; Shah, Ahmed (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The integration of Information and Communication Technology (ICT) in education has transformed teaching and learning practices, particularly in diverse classrooms where students have varying learning needs, backgrounds, and abilities. Traditional instructional methods often fail to address these differences effectively, highlighting the need for adaptive and technology-driven educational approaches. ICT provides opportunities for personalized learning, real-time feedback, and interactive engagement, fostering improved student outcomes across multiple disciplines. This study aims to assess the impact of ICT integration on student performance, engagement, and overall learning effectiveness in diverse classroom settings. A mixed-methods research approach was employed, combining quantitative analysis of student achievement data with qualitative insights from teacher observations and student feedback. Findings indicate that ICT-enhanced learning environments lead to increased student participation, better knowledge retention, and improved problem-solving skills. Statistical analysis revealed a strong correlation between ICT adoption and higher academic performance, particularly in STEM subjects. The study concludes that ICT integration is a crucial factor in modern education, promoting equity, accessibility, and personalized learning experiences. Future research should explore long-term impacts of ICT-driven instruction and strategies for optimizing technology use in different educational contexts.